Methodology for building RPG games to raise awareness of interdisciplinary collaboration among healthcare professionals - Márcio da Silva Camilo; Claudia Lage Rebello da Motta (Journal on Interactive Systems)
Problems in communication and fragmentation in teamwork can cause adverse events in health services, including resulting in deaths. The interdisciplinary training of health professionals can bring robustness and quality to hospital work. However, how can we provide experiences that raise awareness of the benefits of cooperation? To achieve this, each team member must have a mature technical-ethical profile, know their role in the team and conflicts must be resolved with in such a way that they become opportunities. Aiming to encourage cooperation, Role Playing Games (RPG) were chosen as they are playful and promote engagement in teamwork. This article presents a methodology for building such games and strategies for developing skills based on roles played in a team. Preliminary results are promising and show that the methodology can be useful in training health professionals.